Application of the Green Fluorescent Protein as a Reporter for Ace1-Based, Two-Hybrid Studies. (July 1999) - Mayer, Gerd; Launhardt, Heike; Munder, Thomas
The two-hybrid system in Saccharomyces cerevisiae is a genetic approach for the detection of protein-protein interactions in vivo. This technology relies on the activity of separated DNA-binding and transactivation domains of specific transcription factors to reconstitute an active transcription factor complex if interacting proteins are fused to these domains. Interactions are consequently detected through the activity of reporter genes. The two-hybrid technology has been successfully applied for the determination of interactions between numerous proteins of several organisms. Conventional reporter systems, such as the β-galactosidase from Escherichia coli, suffer from a variety of drawbacks, including the requirement for external substrates. In this report, we describe an alternative version of the two-hybrid system using the combined advantages of the copper-inducible transcription factor Ace1 together with the yeast metallothionein gene CUP1 and the green fluorescence protein from aquatic invertebrates as reporters. This technique allows the copper-dependent monitoring of protein-protein interactions in living yeast cells.